"Slaying Ghosts in the Room": Identity Contingencies, Teacher Licensure Testing Events, and African American Preservice Teachers. Issue 7 (July 2014) - Petchauer, Emery
Background: In 41 states, students must pass the "basic skills" portion of their licensure exam before they can be admitted into a teacher education program. Because African American test takers are roughly half as likely to pass basic skills exams on their first attempt compared to White test takers, this portion of the licensure exam is a key gatekeeper to the field and directly shapes the racial diversity of the profession. Researchers generally frame this problem in one of two opposing ways: (a) by locating the cause in skill and knowledge deficiencies of test takers or (b) by locating the cause in the cultural bias of standardized test instruments. This study looks beyond these two polarized views to conceptualize the licensure exam as a testing event that includes a nexus of cognitive and affective processes beyond the specific skills the test is designed to measure. Focus of Study: The study examined the subjective and social psychological ways African American test takers experience teacher licensure testing events. This study was guided by the following research questions: (a) How do African American preservice teachers experience the licensure testing event? (b) How does race become a salient aspect of the testing event experience for African American preservice teachers? The study drew from the social psychological constructs of identity contingencies and situational cues to analyze students' experiences in the testing event. Setting and Participants: Participants in this study were 22 African American preservice teachers attending a predominantly and historically Black institution in the northeastern United States. Each of the participants took the paper format basic skills exam in either the spring 2009 or spring 2010 national administration. Research Design: Drawing from culturally sensitive research practice, this study used a qualitative case study research design to explore test takers' experiences in the testing event. Findings/Conclusions: Findings illustrate how the licensure testing event can become a racialized experience for some participants through (a) interactions with test proctors and site administrators before and during examinations and (b) actions of other test takers that inadvertently signaled racial stereotypes about test preparation, intelligence, and character. Racialized experiences for participants were not based upon any specific test questions or content. Findings are discussed in light of previous research to suggest that these experiences have the capacity to produce a host of cognitive and affective states that undermine performance.